Are foreign investors attracted to weak environmental regulations? : Evaluating the evidence from China - Dean, Judith Myrle, 1956- 1956- (Policy research working paper, 2005)
"One of the most contentious debates today is whether pollution-intensive industries from rich countries relocate to poor countries with weaker environmental standards, turning them into "pollution havens." Empirical studies to date show little evidence to support the pollution haven hypothesis, but suffer potentially from omitted variable bias, specification, and measurement errors. Dean, Lovely, and Wang estimate the strength of pollution-haven behavior by examining the location choices of equity joint venture (EJV) projects in China. They derive a location choice model from a theoretical framework that incorporates the firm's production and abatement decision, agglomeration, and factor abundance. The authors estimate conditional logit and nested logit models using new data sets containing information on a sample of EJV projects, effective environmental levies on water pollution, and estimates of Chinese pollution-intensity for 3-digit ISIC (International Standard Industrial Classification) industries. Results from 2,886 manufacturing joint venture projects from 1993--96 show that EJVs from all source countries go into provinces with high concentrations of foreign investment, relatively abundant stocks of skilled workers, concentrations of potential local suppliers, special incentives, and less state ownership. Environmental stringency does affect location choice, but not as expected. Low environmental levies are a significant attraction only for joint ventures in highly-polluting industries with partners from Hong Kong, Macao, and Taiwan (China). In contrast, joint ventures with partners from OECD sources are not attracted by low environmental levies, regardless of the pollution intensity of the industry. The authors discuss the likely role of technological differences in explaining these results.